(untitled) (Journal of Informatics and Mathematical Sciences, 2017)
Research has shown that air pollution in most of cities and towns in West Africa becoming critical. This research is an ongoing work in West African cities to determine the level of pollution. A fifteen years dataset was obtained from the Multi-angle Imaging Spectro-Radiometer (MISR). Computational and statistical analysis was adopted. The percentage of increased of aerosols loading in 2000, 2004, 2008 and 2012 was 12.2%, 9%, 11.9% and 9%. The cumulative increase of aerosol loading within 15 years was 1.8%. These results show that Binkolo is currently having excess deposition of anthropogenic particulates into the atmosphere.